Diseño de una línea de utensilios. Caso de estudio: Mercados del centro de Ambato, Ecuador - Erick Daniel Andagana Toapanta (2024)
Cookware design is a multifaceted process that combines functionality, ergonomics, and aesthetics to create tools that facilitate and enhance food preparation. This field ranges from selecting durable and safe materials to creating methods that maximize user comfort and efficiency. The objective of this project is to design a line of ergonomic utensils for cooks working in the markets of downtown Ambato, to reduce the risk of wrist injuries. Ergonomics in the culinary environment, the use of traditional materials such as wood, and industrial and artisanal manufacturing techniques are the three main themes of the study. Field studies were conducted to analyze cooks' working conditions and repetitive movements, and the characteristics of conventional materials were examined to evaluate their suitability for ergonomic utensil design. Through bibliographic documentary research, relevant information on utensil design was collected, employing methodologies such as the QFD matrix, DCU and ME the Donald Norman to prioritize the user and resolve contradictions in the project. The completion of observation sheets and interviews with 10 professionals in the field allowed for an exhaustive analysis of the environment and specific needs. The results obtained favor the workers of the central market of Ambato, achieving a significant reduction in wrist pain and injuries, improvements in the work efficiency of the cooks, and a high cultural acceptance of the new utensils. Likewise, the productive sector benefits from the commercialization of these kitchen utensils.